2018
DOI: 10.7717/peerj.4939
|View full text |Cite
|
Sign up to set email alerts
|

3D skeletal muscle fascicle engineering is improved with TGF-β1 treatment of myogenic cells and their co-culture with myofibroblasts

Abstract: BackgroundSkeletal muscle wound healing is dependent on complex interactions between fibroblasts, myofibroblasts, myogenic cells, and cytokines, such as TGF-β1. This study sought to clarify the impact of TGF-β1 signaling on skeletal muscle cells and discern between the individual contributions of fibroblasts and myofibroblasts to myogenesis when in co-culture with myogenic cells. 3D tissue-engineered models were compared to equivalent 2D culture conditions to assess the efficacy of each culture model to predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 40 publications
0
24
0
1
Order By: Relevance
“…Our histology and mechanical testing suggest that although cultured meats based on BAOSMC or RbSkMC show some similarities to natural meats, further work with improved skeletal myoblast differentiation are required to more closely recapitulate the mature contractile architecture observed in natural muscle. Prior work by our laboratory and others demonstrated that recapitulating natural muscle phenotypes in culture required biomimetic culture conditions 36,5763 that account for substrate stiffness 57 and biochemistry, 58 anisotropic muscle alignment, 36,62 and chemical factors secreted by supporting cell types. 63 For these reasons, recapitulating the nutritional profiles of meat will likely require building on bioengineering strategies 64 that account for multiscale engineering of genetic and epigenetic factors, as well as cell–material and cell–cell interactions that contribute to tissue development.…”
Section: Discussionmentioning
confidence: 99%
“…Our histology and mechanical testing suggest that although cultured meats based on BAOSMC or RbSkMC show some similarities to natural meats, further work with improved skeletal myoblast differentiation are required to more closely recapitulate the mature contractile architecture observed in natural muscle. Prior work by our laboratory and others demonstrated that recapitulating natural muscle phenotypes in culture required biomimetic culture conditions 36,5763 that account for substrate stiffness 57 and biochemistry, 58 anisotropic muscle alignment, 36,62 and chemical factors secreted by supporting cell types. 63 For these reasons, recapitulating the nutritional profiles of meat will likely require building on bioengineering strategies 64 that account for multiscale engineering of genetic and epigenetic factors, as well as cell–material and cell–cell interactions that contribute to tissue development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its central role in muscle development, TGF-β contributes to mature skeletal muscle mass, and is a key regulator of intramuscular fibrogenesis (Kollias and McDermott, 2008;Miao et al, 2016). In addition, it was shown that TGF-β1 suppressed myogenesis in 2D cultures, while enhancing myogenesis in 3D cultures, rendering it a valuable regulator of in-vitro muscle tissue development (Krieger et al, 2018). Myogenesis can be induced by substrate stiffness (Levy-Mishali et al, 2009;Syverud et al, 2014), IGFs and myogenic miRNA (Vitello et al, 2004;Yin et al, 2013), or by inhibition of anti-myogenic GFs produced by nearby cells (Christov et al, 2007;Yin et al, 2013).…”
Section: Satellite Cells and Myogenesismentioning
confidence: 99%
“…Fibroblast and myofibroblasts (Baum and Duffy, 2011) are simple to isolate and grow, and have a short cell cycle. They were shown to promote vascularization and muscle development in tissue engineered constructs (Shandalov et al, 2014;Ciccone, 2015;Mackey et al, 2017;Krieger et al, 2018), and are considered to have an important role in clean meat production (Pandurangan and Kim, 2015). However, isolated fibroblasts are usually not very well defined, and are often comprised of several subpopulations with few specific markers (Chapman et al, 2016).…”
Section: Fibroblasts and Ecmmentioning
confidence: 99%
“…In the past 5 years, research focused on cell-based meats has accelerated from the tasting of the cell-cultured hamburger in 2013 (Zaraska, 2013) and early publications, including lifecycle assessments and basic research (Tuomisto and Teixeira de Mattos, 2011;Post, 2012Post, , 2014, to a growing start-up community, updated life cycle assessments, and publications focused on refining the technologies required to accelerate cellbased meat production (Tuomisto et al, 2014;Krieger et al, 2018;Rubio et al, 2019). To date, research decisions in cell-based meat production, such as selection of cell species and cell type have been largely driven by market size and environmental impact (Rodriguez-Fernandez, 2019), rather than suitability of cells species and types suitable for large scale bioreactor cultivation.…”
Section: Cell-based Seafood Productionmentioning
confidence: 99%